Institutional sustainability strategy of farmers in red onion farming - Syarif, Asriyanti; Mudatsir, Rasdiana (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2023)
Farmer participation will continue to be sustainable, so an institutional sustainability strategy is needed to develop agriculture as a support for the Indonesian economy. This study took informants from farmer groups and extension agents which were carried out purposively. Data collection was carried out by conducting in-depth interviews through the FGD (Focus Group Discussion) mechanism. Data analysis was carried out in a qualitative descriptive manner to answer the institutional goals of support and participation while the sustainability strategy was carried out by adopting a variant of Brinkerhoff's theory of sustainability strategy. Supporting institutions in red onion farming are farmer groups and extension workers who synergize with each other. Participation of group members: decision making and technological innovation by 40%, providing advice and input by 80% and utilizing local wisdom by 100%. The mechanical sustainability strategy follows group procedures based on SOPs and is active in the process. Adaptive strategy by providing knowledge about the impact of climate change. Interactive strategy by providing input on sustainable agriculture such as: the use of organic fertilizers. While the reactive strategy is carried out by using technology from innovation and the adoption process.